Characterizing heterogeneity in motivational impairments in psychosis - Lewandowski, Kathryn E.; Luo, Jintian; Yao, Beier; Whitton, Alexis E. (Frontiers in Psychiatry, 2025)
IntroductionMotivational impairments are a hallmark symptom of psychotic disorders. However, motivation is a multidimensional construct believed to be underpinned by different neural mechanisms and differentially impaired both between and within diagnostic groups. We used a data driven approach to identify different motivational profiles in people with psychosis.MethodsParticipants (n=242) included people with a diagnosis of a DSM-V schizophrenia spectrum disorder (SSD; n=95), mood disorder with psychosis (MDP; n=95), and healthy controls (n=52). Participants were assessed using the Behavioral Inhibition/Behavioral Activation Scales (BIS/BAS), measures of clinical symptoms, assessments of hedonic capacity (anticipatory and consummatory pleasure; TEPS), and a behavioral task of effort expenditure for reward. The four BIS/BAS subscales from the patient groups were normed to the controls and entered first into a hierarchical cluster analysis, and then into K-means cluster analysis for the final cluster solution. ResultsA four-cluster solution best fit data, reflecting: a High Avoidance group (n=56); a High Approach group (n=66); a Low Approach/High Avoidance group (n=26); and a Low Approach group (n=35). Diagnostic groups were represented in each cluster. Clusters differed on depression and anxiety severity on both interview-based and self-report measures, as well as on anticipatory and consummatory pleasure. Contrary to our hypothesis, groups did not differ on a measure of community functioning. DiscussionThese findings suggest that aspects of approach and avoidance motivation may be both uniquely and additively associated with anxiety, depression, and hedonic experiences. Characterization of motivational profiles may help parse heterogeneity in motivation and predict other important aspects of illness.